Optical interferometry to investigate the heat transfer from a vertical cone under air jet impingement. (April 2015) - Borjian, E.; Yousefi, T.; Ashjaee, M.
Abstract: The laminar forced convection heat transfer from an isothermal vertical cone under impingement of air jet was investigated experimentally. In the experiment a Mach–Zehnder interferometer was used to obtain the local heat transfer coefficients. The cone with tip angle of 45° has been suspended from its base vertically. The round jet impinged to the tip of the cone from an orifice with 6 mm diameter. The Reynolds number based on the orifice diameter was varied from 1570 to 3040. Furthermore, the ratio of orifice-cone tip distance to orifice diameter, H / d, was varied from 1 to 6. The results show that the average Nusselt number increases by increasing the Reynolds number and by decreasing the distance between the jet exit and cone tip. Based on the experimental results, a correlation is proposed for average Nusselt number in terms of Reynolds number and jet exit spacing from the cone tip. In addition, from the local Nusselt number it can be seen that for low Reynolds numbers there is an increase in the local heat transfer at the base of the cone. Highlights: Using Abel equation the results are in good agreement with previous works. Mach–Zehnder interferometer was used to investigate the jet flow over a cone. A correlation has been obtained for local heat transfer coefficient.